Strategi Inovatif Peningkatan Ekonomi Warga Desa Desa Peh Wetan - Lidiawan, Angga Rizka; Sudjiono, Sudjiono; Subianti, Tutut; Hariyati, Alma (Jurnal ABM Mengabdi, 2025)
This aims to enhance the local economy through an entrepreneurial approach and the use of technology. Training was provided to community members on business management, digital marketing, and technology-based financial management to strengthen micro, small, and medium enterprises (MSMEs). By utilizing social media and e-commerce platforms, MSME owners were able to expand their markets, which were previously limited to local areas. The results of the program show that 75% of participants experienced an increase in income, mainly due to newly acquired knowledge in business management and digital marketing. Additionally, product diversification has started to develop, with some participants creating new products that are more aligned with current market trends. The success of this program demonstrates the importance of innovation and technology in driving local economic growth, as well as strengthening the economic resilience of rural communities. In the future, it is hoped that similar training programs can be expanded to reach more communities, creating sustainable economic development.